Pharmacokinetics of S-EPA, and its inhibition on indoleamine 2, 3-dioxgenase: a case of sulfur-substitution affecting distributions in blood cells. (2nd November 2019) - Wang, Wenyan; Zhuang, Xuhui; Sun, Heyuan; Dong, Lina; Liu, Zongliang; Du, Guangying; Ye, Liang; Tian, Jingwei
Abstract: 1. S-EPA is a sulfur-substitution analog of epacadostat (EPA), an effective small molecule indoleamine 2, 3-dioxgenase1 (IDO) inhibitor. By in vitro and in vivo experiments, pharmacokinetic differences of two closely related analogs, S-EPA and EPA was investigated in this study. 2. Liver microsomes clearance experiments showed S-EPA had comparable metabolic stability with EPA in rat and human liver microsomes. The whole blood distribution experiments showed the distribution ratio of S-EPA in blood cells to plasma in mice, rats, dogs and monkey was 1.2, 4.8, 2.2 and 40.6, respectively. While the distribution ratio of EPA ranged from 0.94 to 1.30 in mice, rats, dogs and was 3.1 in monkeys. 3. The pharmacokinetic study in rats showed the exposure (AUClast ) of S-EPA in plasma and blood cells was 1.7-fold and 3.9-fold higher than that of EPA, respectively. Moreover, the exposure ratio of S-EPA in blood cells to plasma was 3.7, while the ratio of EPA was 1.6. 4. In CT26 tumor bearing mice, the IDO inhibition of S-EPA and EPA on plasma or tumor kynurenine was generally consistent. And the inhibition ratio could reach at more than 50% at 3 h after single dose, at least lasting up to 8 h.